2007
DOI: 10.1016/j.ajog.2007.08.064
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of pelvic floor repair after hysterectomy: A population-based cohort study

Abstract: OBJECTIVE-The objective of the study was to assess the incidence of and risk factors for pelvic floor repair (PFR) procedures after hysterectomy. RESULTS-The cumulative incidence of PFR after hysterectomy was 5.1% by 30 years. This risk was not influenced by age at hysterectomy or calendar period. Future PFR was more frequently required in women who had prolapse, whether they underwent a hysterectomy alone (eg, vaginal [hazard ratio (HR) 4.3; 95% confidence interval (CI) 2.5 to 7.3], abdominal [HR 3.9; 95% CI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 24 publications
1
64
1
4
Order By: Relevance
“…This is supported by data from Blandon et al, 131 who reported that, in comparison with women without prolapse, women who had a hysterectomy for prolapse were at increased risk for subsequent pelvic floor repair.…”
Section: Interpretation Of Findingssupporting
confidence: 77%
“…This is supported by data from Blandon et al, 131 who reported that, in comparison with women without prolapse, women who had a hysterectomy for prolapse were at increased risk for subsequent pelvic floor repair.…”
Section: Interpretation Of Findingssupporting
confidence: 77%
“…Interestingly, a rectocele appears in combination with an intussusception in about 16% of patients after a hysterectomy and is a consequence of a weakened pelvic floor [11]. However, the effect of a hysterectomy on POP has been debated, with no consensus to date [12][13][14].…”
Section: Introductionmentioning
confidence: 97%
“…This is likely because the apical compartment is exposed at the time of surgery, improving access for apical suspension during closure of the vaginal cuff. In addition, published evidence has demonstrated the importance of concomitant apical suspension at the time of hysterectomy as treatment for uterovaginal prolapse [8,18,19]. The American Congress of Obstetricians and Gynecologists has incorporated this evidence into published guidelines supporting routine apical suspension at the time of hysterectomy for women with pelvic organ prolapse [20].…”
Section: Discussionmentioning
confidence: 99%